Neuronal Intranuclear Inclusion Disease Presenting with Acute-Onset Dementia and Cortical Edema: A Case Report - Feng, Xiao; Li, Yue; Zhao, Qin; Xu, Shabei (Frontiers in Neurology, 2024)
Background Neuronal Intranuclear Inclusion Disease (NIID) is a neurodegenerative disorder characterized by the formation of eosinophilic inclusions in the neurons, visceral and skin cells. The cause is associated with the GGC nucleotide repeat expansion in the NOTCH2NLC gene. The imaging hallmark of NIID is hyperintensities on diffusion-weighted imaging (DWI) at the corticomedullary junction. Clinical manifestations of NIID are highly heterogeneous. Here, we report a case of NIID presenting with acute-onset dementia and cortical edema. Case presentation We describe an elderly male patient who presented with sudden dementia within a day. Considering the abrupt onset and the stroke history, we initially diagnosed vascular disease. However, further imaging revealed cortical edema in the temporo-parieto-occipital lobes. Blood and cerebrospinal fluid tests ruled out immunological, metabolic, infectious, or neoplastic etiologies. Genetic testing ultimately confirmed the diagnosis of NIID. Intravenous immunoglobulin (IVIG) therapy did not improve the patient’s symptoms; However, about 1 month after treatment, spontaneous improvement was observed. It is noteworthy that 22 months before the onset of cognitive impairment, the patient’s MRI for headaches already exhibited the typical imaging lesions of this disease in the cerebellum paravermal region. Conclusion Patients with encephalopathy syndrome exhibiting imaging features resembling mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome or Creutzfeldt-Jakob disease should consider the NIID as differential diagnosis. Chronic headaches and symmetric lesions in the cerebellar paravermal region on MRI may be noteworthy indicators of NIID during non-episodic phases.